Culture and Power in Revolutionary Russia - Read, Christopher. author. aut Link
XII, 266 p.
Keywords: This book shows that the rise of the intelligentsia occurred earlier than is normally thought, and that by 1922, rather than 1932, the underlying principles of the new Soviet government's policies towards culture had already emerged and "proto-Stalinism" was increasingly important.